Assessing Value for Money: the Oxford Policy Management Approach - King, Julian; Daniel Wate; Esther Namukasa; Alex Hurrell; Frances Hansford; Patrick Ward; Shiva Faramarzifar (Oxford Policy Management, 2023)
This document offers practical guidance for assessing the Value for Money (VfM) of government- and donor-financed programmes and policy interventions. In line with OPM’s focus and mission, it has been predominantly applied in the international development sector, but the approach upon which it is based is also used in the context of domestic public policy and programmes.1 There is increasing scrutiny on VfM in international development, but a lack of appropriate methods to support its assessment. There is a risk of reaching invalid conclusions if VfM evaluation is tied to a narrow set of indicators devoid of any evaluative judgement—for example, by emphasising the most readily quantifiable measures rather than the most important (but harder to quantify) aspects of performance, or by focusing on the quantification of outputs and outcomes at the expense of more nuanced consideration of their quality, value, and importance. The approach presented in this guide combines theory and practice from evaluation and economics to respond to requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management. It involves developing and implementing a framework for: • organising evidence of performance and VfM; • interpreting the evidence on an agreed basis; and • presenting a clear and robust performance story. This guide sets out a framework for making and presenting judgements in a way that opens both the reasoning process and the evidence to scrutiny. The approach is designed to be used in alignment with broader monitoring, evaluation, and learning (MEL) systems—both for efficiency's sake, and to ensure conceptual coherence between VfM evaluation and wider MEL work. The VfM framework achieves these aims by: • using explicit criteria (aspects of performance) and standards (levels of performance) to provide a transparent basis for making sound judgements about performance and VfM; • combining quantitative and qualitative forms of evidence to support a richer and more nuanced understanding than can be gained from the use of indicators alone; • accommodating economic evaluation (where feasible and appropriate) without limiting the analysis to economic methods and metrics alone; and • incorporating and building on an approach to VfM evaluation which is familiar to international aid donors.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.